Negara Sejahtera dan Batas Inklusivitas Pendidikan: Studi tentang Kerajaan Brunei Darussalam - Samsuddin Alamsyah; Achmad Uzair Fauzan (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2026)
This study is motivated by an interest in examining social inequality within a relatively prosperous society such as the Sultanate of Brunei Darussalam. Widely recognized as a country with high per capita income and relatively comprehensive welfare services, Brunei nevertheless continues to face social challenges, particularly in relation to ethnic communities and other marginalized groups. The objective of this study is to analyze Brunei Darussalam’s educational policy strategies and their relationship to addressing social inequalities experienced by marginalized communities within the country. This research employs a qualitative method using a library research approach through the analysis of formal literature and grey literature, particularly state documents concerning Wawasan Brunei 2035 and its implementation reports. The findings indicate that, on the one hand, the Brunei government has implemented comprehensive policies aimed at improving human resource quality and social mobility, including free education up to the university level, overseas scholarship programs, and the strengthening of curricula grounded in the values of Melayu Islam Beraja (MIB). In addition, labor market integration programs through JobCentre have been introduced to reduce unemployment. On the other hand, however, this study also identifies structural challenges in the form of unequal access for certain groups, policy biases toward ethnic minorities, and disparities between regions and educational quality. Therefore, although Brunei’s educational policies possess significant potential to reduce social inequality, further evaluation and reform are required in order to create a more inclusive and equitable educational system.